Karakteristik rumah tangga miskin di Daerah Istimewa Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
Abstract The proximate of poverty level is based on expenditure per individual member of a household. The low expenditures are primarily found among households engaged in labouring activities or in agricultural sector. The consequences of a low expenditure or income is the inability of the household in providing appropriate needs for its members, including access to informations and schooling. An enhancement of human resources development and promotion of equal access to the remunerative activities are among alternatives of raising the low income households. Keywords: rumah tangga miskin